2015
DOI: 10.3389/fncel.2015.00229
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of bradykinin B1 and B2 receptors in neonatal rat trigeminal ganglion neurons

Abstract: Bradykinin (BK) and its receptors (B1 and B2 receptors) play important roles in inflammatory nociception. However, the patterns of expression and physiological/pathological functions of B1 and B2 receptors in trigeminal ganglion (TG) neurons remain to be fully elucidated. We investigated the functional expression of BK receptors in rat TG neurons. We observed intense immunoreactivity of B2 receptors in TG neurons, while B1 receptors showed weak immunoreactivity. Expression of the B2 receptor colocalized with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(42 reference statements)
0
13
1
Order By: Relevance
“…We therefore concluded that B 1 receptors in TG neurons, similar to those elsewhere in the brain, show high selectivity for Lys-[Des-Arg 9 ]BK [3]. In addition, the activation of B 2 receptors induced both the influx of Ca 2+ from the extracellular medium and the release of Ca 2+ from intracellular Ca 2+ stores [3]. However, the intracellular signaling pathway by which Lys-[Des-Arg 9 ]BK induces Ca 2+ mobilization in response to the activation of B 1 receptors had not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…We therefore concluded that B 1 receptors in TG neurons, similar to those elsewhere in the brain, show high selectivity for Lys-[Des-Arg 9 ]BK [3]. In addition, the activation of B 2 receptors induced both the influx of Ca 2+ from the extracellular medium and the release of Ca 2+ from intracellular Ca 2+ stores [3]. However, the intracellular signaling pathway by which Lys-[Des-Arg 9 ]BK induces Ca 2+ mobilization in response to the activation of B 1 receptors had not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 71%
“…In a previous study [3], we demonstrated functional expression of B 1 and B 2 receptors in TG neurons, observing that BK elicited increases in intracellular free Ca 2+ concentration ([Ca 2+ ] i ) that were inhibited by B 2 receptor antagonists, but not by B 1 receptor antagonists, whereas application of Lys-[Des-Arg 9 ] BK induced increases in [Ca 2+ ] i that were sensitive to a B 1 receptor antagonist. We therefore concluded that B 1 receptors in TG neurons, similar to those elsewhere in the brain, show high selectivity for Lys-[Des-Arg 9 ]BK [3]. In addition, the activation of B 2 receptors induced both the influx of Ca 2+ from the extracellular medium and the release of Ca 2+ from intracellular Ca 2+ stores [3].…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations